Dokter Spesialis Geriatri Sebuah Profesi Baru Di Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT The number of the elderly is increasing. In the year of 2000 the number in Indonesia will be about 23 million or about 11 % of all Indonesia. It is predicted that in 2020 Indonesia will be the fourth country in the world that has many elderly, meanwhile in Yogyakarta the number was about 317,043. While doctors specializing on child health in Yogyakarta is about 30 doctors and they work for about 804,038 children, there is no doctor specializing on geriatrics for 314,043 elderly. Therefore, education for doctors specializing on geriatrics is really needed.